Research Data Management Practices: Preparedness and Challenges among Librarians in Nigeria - Alex-Nmecha, Juliet C.; Onifade, Abdurrahman B. (Ghana Library Journal, 2023)
There is a global deluge in research data generation in academia and industries as a result of the proliferation of modern information and communication technologies (ICTs). This data deluge has raised concerns that research data be properly managed for easy accessibility, retrieval, use, and reuse for scientific progress. Funding agencies and institutions have gradually set standards or requested researchers to provide necessary data management plans for their research. Based on these backgrounds, this study sought to investigate research data management (RDM) practices, the level of preparedness, and the challenges being faced by librarians in Nigeria. The study adopted a survey research design of quantitative methodology. Questionnaire developed using Google Forms and administered electronically on LIS platforms, was used for data collection from librarians across the six geopolitical zones in Nigeria. The data collected was presented in charts and analysed descriptively. Findings from the study show that lack there is a lack of awareness about RDM policy, and skills to organise research data among librarians. The study recommends the formulation of comprehensive RDM policies, awareness campaigns, and professional development initiatives to address these challenges, fostering a culture of effective RDM in Nigeria.